2013
DOI: 10.1080/03601234.2013.824285
|View full text |Cite
|
Sign up to set email alerts
|

Oxidative stress, hematological and biochemical alterations in farmers exposed to pesticides

Abstract: In this study, a cohort of farmers from the Mateur region in the North of Tunisia, were interviewed and examined for the biochemical effects of pesticides. We studied their haematological profile, lipid parameters, serum markers of nephrotoxicity and hepatotoxicity. We also evaluated the activities of Butyrylcholinesterase (BChE), Acetylcholinesterase (AChE) and thiolactonase-paroxonase (PON). Moreover, lipid peroxidation and activities of antioxidant enzymes superoxide dismutase (SOD) and catalase (CAT) were … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

10
48
0
2

Year Published

2015
2015
2022
2022

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 65 publications
(60 citation statements)
references
References 57 publications
10
48
0
2
Order By: Relevance
“…were also reported. The inhibited AChE and BChE activity associated with cholinergic dysfunctions including adverse neurobehavioral outcomes in pesticide‐exposed workers has been determined in some studies . In the present study, the activity of AChE is found to be significantly decreased in pesticide‐exposed agriculture workers consistent with the previous findings …”
Section: Discussionsupporting
confidence: 91%
See 3 more Smart Citations
“…were also reported. The inhibited AChE and BChE activity associated with cholinergic dysfunctions including adverse neurobehavioral outcomes in pesticide‐exposed workers has been determined in some studies . In the present study, the activity of AChE is found to be significantly decreased in pesticide‐exposed agriculture workers consistent with the previous findings …”
Section: Discussionsupporting
confidence: 91%
“…Besides, other health effects including headache, nausea, vomiting, pupillary constriction, tearing, salivation, and so forth, have also been frequently reported . Further, alterations in the hematological parameters such as decrease size of red blood cells, higher platelets and white blood cell (WBC) counts and increased activities of gamma‐glutamyltransferase (GGT), alkaline phosphatase (ALP), bilirubin has been shown to be linked with hepatic cell damage in human occupationally exposed to the pesticide . Conversely, nephrotoxic changes as evidenced by elevated levels of plasma urea, uric acids and creatinine in workers occupationally exposed to pesticides have also been reported …”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…Thus, if the farmers spray with WHO Class I pesticides, or spray for longer than the 2 h that are considered to reflect farmers’ usual spraying time [27, 34, 36], while applying unsafe work practices, a considerable risk of acute organophosphate poisoning can be expected. Furthermore, long-termed exposure to low doses of hazardous pesticides are linked to adverse health effects in immune, hematological, nervous, endocrine and reproductive systems as well as DNA damage [2, 16]. Thus, interventions promoting safe work practices reducing farmers’ hazardous pesticide exposure are needed to reduce farmers’ risk of acute pesticide poisoning and chronic sequelae of pesticide exposure.…”
Section: Discussionmentioning
confidence: 99%